Analysis of Learning System in Higher Collection through a Technology 4.0 Approach in the Era of Covid-19 Pandemic - Mesterjon Mesterjon; Suwarni Suwarni; Diah Selviani; Sori Monang (Yayasan Keluarga Guru Mandiri, 2022)
Analysis of learning management in higher education through a technology 4.0 approach. This study aims to obtain an overview of the implementation of learning management with a communication information technology approach (technology 4.0) to improve the learning management system in universities, especially the Bengkulu province UNIVED campus during the covid 19 pandemic. This research will be investigated further and more carefully on management factors. The results showed that: The availability of ICT network infrastructure services on the Unived campus was obtained by 80% of students and 93% of the academic community. In x2 (Availability of Student Academic Information Systems) on the Unived campus, the results of interviews were 82% of students and 94% of the academic community. In x3 (Availability of e learning applications) on the Unived campus, the results of interviews were 78% of students and 92% of the academic community. Based on the comparison of test data and interview data on the PT Unived campus, it was concluded that the Learning System (LS) = x in stages (ISM) = (A, C, and D) experienced an increasing trend (positive). Meanwhile, in the Individual stages of mastering ICT (B) there is a downward trend.